Research on Wheel Polygonization Based on Rail Modal Oscillation Analysis - LI Dadi; DAI Huanyun (机车电传动)
Based on the dynamic test data, the vibration level and vibration transmission of the components of the bogie with wheel polygonization were analyzed. The typical frequency characteristics of the vibration of the bogie caused by wheel polygonization were provided, and the influence of polygon wear on adjacent wheelset was analyzed. Based on the Timoshenko theory and the transfer matrix method, the vibration equation of the rails in the range of two wheelsets was deduced and the modal vibration characteristics were analyzed. The influence of the boundary conditions and temperature on the mode of the rail was discussed. The source of wheel polygonization frequency was analyed. And based on the parameter of Wuhan-Guangzhou and Haerbin-Dalian high-speed railway, the third-order vertical bending frequency of the rail coincided with the wheel polygonization frequency, which provided basis for the mechanism study of wheel polygonization.